The Effect of Self-Control on Employee Performance with Cyberloafing as a Moderating Variable - Alexander Wirapraja; Novi Tri Hariyanti (University of Merdeka Malang, 2025)
Employee conduct significantly impacts an organization's performance and productivity, as employees are valuable resources essential to the sustainability of company operations. This study aims to examine the effect of self-control on employee performance, with cyberloafing behavior acting as a mediator. Cyberloafing refers to the personal use of technology for non-work-related activities during office hours. The study involved 118 respondents working at firm X in Trosobo Sidoarjo, using a purposeful sampling technique and distributing questionnaires. The findings show that employee performance and self-control are interrelated; however, cyberloafing behavior does not directly affect employee performance. While self-control plays a crucial role in enhancing performance, cyberloafing behavior is not a significant mediator in this relationship. Based on these results, the study suggests that companies should enhance their supervisory functions and provide self-development training programs focused on emotional management and self-control. These programs would help employees manage their behavior effectively in the workplace, minimize the occurrence of cyberloafing, and improve overall work productivity. This approach can support a healthier, more productive work environment, benefiting both individual employees and the organization as a whole.